Review of Cape Verde Pselactus Broun, 1886 (Coleoptera: Curculionidae: Cossoninae) with description of a new species, larvae and notes on biology - Skuhrovec, Jiří; Hlaváč, Peter; Batelka, Jan (Zootaxa, 2017)
The genus Pselactus in the Cape Verde Islands is reviewed. Pselactus obesulus (Wollaston, 1867) from São Vicente is redescribed and P. strakai sp. nov. from São Nicolau is described. Both species are diagnosed and illustrated; their larvae are described, larval morphology is discussed and the current state of knowledge about immature stages of Cossoninae is summarized. The systematic position of the genus within Onycholipini is reviewed, and the placement of genus in Cossoninae is discussed. A short note on biogeography of Pselactus is provided.